Ventilator-associated pneumoniaMechanical ventilation pneumoniaAnd its risk factors - Jimenez Vega, Camilo Alberto; Accoce, Matías (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Ventilator-associated pneumonia (VAP) is a lung infection that occurs in patients who are being mechanically ventilated. Risk factors include a prolonged duration of mechanical ventilation, a weakened immune system, and a previous history of infections. Early diagnosis of pneumonia is important for effective treatment and faster recovery. Diagnostic methods include taking X-rays, performing cultures of respiratory secretions, and evaluating the patient’s symptoms. Objective is to carry out a systematic review that can give alarm guidelines in the pathophysiological behavior of patients with pneumonia associated with ventilation. Mechanics, identify and act promptly to reduce mortality. Material and methods: A systematic review was carried out, of the papers that contained material that will help us meet the objective, to study pneumonia associated with mechanical ventilation and evaluate its pathophysiology